2019
DOI: 10.1177/0898264319893486
|View full text |Cite
|
Sign up to set email alerts
|

Informal and Formal Social Integration Shape Eating and Drinking of Older Black and White Americans

Abstract: Objective: Health behaviors are seen as one possible pathway linking race to health outcomes. Social integration has also been consistently linked to important health outcomes but has not been examined as a mechanism accounting for racial differences in health behaviors among older U.S. adults. Method: We use data from the American’s Changing Lives (ACL) Study to explore racial differences in measures of social integration and whether they help account for racial differences in several dietary behaviors and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…In this sample, time spent with family was related to fruit and vegetable consumption, but time spent with friends was not. Our findings align with those of similar studies in adults, where social integration was found to be a substantial predictor of fruit and vegetable consumption [ 14 ]. Our results suggest that social integration, specifically time with family, appears to be a large predictor of diet behaviors in youths.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this sample, time spent with family was related to fruit and vegetable consumption, but time spent with friends was not. Our findings align with those of similar studies in adults, where social integration was found to be a substantial predictor of fruit and vegetable consumption [ 14 ]. Our results suggest that social integration, specifically time with family, appears to be a large predictor of diet behaviors in youths.…”
Section: Discussionsupporting
confidence: 93%
“…For example, social integration influences PA, both cross-sectionally and longitudinally, where informal social integration with friends appears to be more predictive of PA than informal social integration with family [ 13 ]. Informal integration also predicts higher fruit and vegetable consumption [ 14 ]. Those who are more socially integrated have higher-quality sleep than those who are less socially integrated [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between religious attendance and health behavior has been assessed in a number of studies. This line of research demonstrates that religious attendance is negatively associated with alcohol consumption among general population samples (Clarke et al 1990), older adults (Hauschildt and Burgard 2019), and African American men (Bowie et al 2017). In addition, religious attendance is also inversely related to a likelihood of smoking in the general population (Gillum 2005), young adults (Guo and Metcalfe 2019), and Texas adults (Hill et al 2006).…”
Section: Theoretical and Empirical Backgroundsmentioning
confidence: 99%
“…In terms of physical exercise, religious attendance is associated with higher levels of exercise among adolescents in Czech (Malinakova et al 2018), Hispanic women (Arredondo et al 2005), and older adults (Gillum 2006). Finally, regarding dietary habits, religious attendance is associated with healthier dietary habits among American youth (Wallace and Forman 1998), older adults (Hauschildt and Burgard 2019) and Hispanic women (Arredondo et al 2005). Given that much of this work has been conducted in the U.S., an effort is made in this study to contribute to the literature by examining the association between religious attendance and health behavior cross-nationally.…”
Section: Theoretical and Empirical Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation